Tabique constructions in the Municipalities Association of Terra Fria do Nordeste Transmontano - Martinho, J. (2012)
Tabique is one of the main Portuguese traditional building techniques which basically use natural and local building materials such as earth and timber. A tabique building component such as a wall is built up using a simple timber structure covered by an earth based mortar on both sides. The earth based mortar has an important role in this building system technology since it not only protects the internal timber structure but it also acts as finishing element. Meanwhile, earth has the advantage of being abundant, natural, local and recycled giving to this technique a special importance in the sustainability context. It has been noticed that this traditional building technique has an expressive incidence in the region of Trás-os-Montes and Alto Douro, Portugal. Taking into account that the Trás-os-Montes and Alto Douro region is very large, there was the necessity to divide it in to more manageable areas. The manageable areas are the six Municipalities Associations, which are: Alto Tâmega, Terra Quente Transmontana, Terra Fria do Nordeste Transmontano, Vale do Douro Norte, Vale do Douro Sul and Douro Superior. This research work is focused on the Municipalities Association of Terra Fria do Nordeste Transmontano. This, combined with the scarcity of scientific studies concerning this type of construction in this region, motivated this research work that uses some constructions as sampling and which is focused on an experimental study to identify the chemical and mineralogical composition of the coating material / filler used, the species of wood and the hardness of the nails.